Marine animals and snakes: their venoms and poisons for therapeutics? - Othman, Iekhsan; Zainal Abidin, Syafiq Asnawi; Abdullah, Nur Atiqah; Shaikh, Mohd Farooq; Ahmad Ismail, Khaldun; Ahmad Rusmili, Muhamad Rusdi; Naidu, Rakesh (2018)
The discovery and modification of angiotensin converting enzyme inhibitor. Angiotensin converting enzyme inhibitor creation starts when Bothrops jararaca venom was found to be causing hypotension by potentiating-bradykinin activity. Bradykinin-potentiating peptides are also found in Viperidea and Elapidea snake species such as Agkistrodon halys pallas, Bothrop jararacussu, Bothriechis lateralis, Bothriechis schlegelii, Macrovipera lebetina and Naja haje haje. Another example are the atrial natriuretic peptides which are hormones that are endogenously released when myocardium is stretched and overload in the body. These peptides cause natriuresis, inhibition of rennin-angiotensin systA tripeptide (Glutamic acid-Valine-Tryptophan) isolated from Bottrop atrox venom has been shown to protect against the dopaminergic neurons loss in Parkinson’s disease model. Similarly, neurotoxins from Mamba performed antagonist activity with acetylcholinesterase receptors that useful in therapeutic of Alzheimer’s disease. A secretory phospholipase A2 from Naja sputatrix reduced neuronal death and promote cell survival in the organotypic hippocampal culture and possess anti-apoptotic effects and recently, an low molecular weight fraction from B. jarararaca showed protection effects against apoptosis of hippocampal cells induced with H2O2. Interestingly, a molecule from South and Central America snake viper, Bothrops asper venom was found to reduce amyloid beta plaque that accumulated in Alzheimer’s disease patient neurons through enhancement Endothelian Converting Enzyme-1 and Neprilysin activity that lead to degradation of amyloid beta protein. These studies showed the potential snake venoms as neuroroprotection or neurotherapeutic source. On the other hand, research on marine organisms have moved from purely chemical exercise of isolating novel structures to a collaborative effort between marine chemists, molecular pharmacologists, and cell biologists. In the advent of the advanced `omics’ technologies in integrative biology, the future of the drug discovery should be enhanced and facilitated. Various bioassays attempting to elucidate the mechanisms between specific enzymes, receptors, and recombinant whole cells are commonly used for identifying marine natural products with potential biomedical uses. This presentation will provide a baseline for further studies on extracting molecules that are potentially importance for therapeutics applications.